Performance Architecture: Processes That Can Kill You. Issue 5 (May 2017) - Addison, Roger; Haig, Carol
Abstract : An error can unwittingly derail a critical process and put its users in mortal danger. While not all processes are deadly if they are poorly executed, many can undermine otherwise successful businesses, putting their survival at risk. By monitoring the life cycle of every process, we can take actions to correct malfunctions before they occur, saving the lives of organizations and sometimes even people.